Pralatrexate in relapsed/refractory T-cell lymphoma: a retrospective multicenter study. Issue 2 (28th January 2021) - Bhurani, Mansi; Admojo, Lorenz; Van Der Weyden, Carrie; Twigger, Robert; Bazargan, Ali; Quach, Hang; Zimet, Allan; Coyle, Luke; Lindsay, Julian; Radeski, Dejan; Hawkes, Eliza; Kennedy, Glen; et al.
Abstract: We present a retrospective multicenter study of pralatrexate treatment outcomes in an Australian practice setting for patients with relapsed/refractory T-cell lymphoma who had failed 1+ systemic therapies, treated via a compassionate access program. Endpoints assessed included response rates, toxicities, and subsequent therapies. Progression-free survival (PFS), time to next treatment (TTNT), event-free survival (EFS), overall survival (OS), and time to best response, were assessed by Kaplan–Meier analysis. The study included 31 patients, with median age 69 years. We demonstrated ORR of 35.5% ( n = 11), including 4 complete responses (13%) and 7 partial responses (23%). The predicted median OS was 10 months, with EFS of 9 months, and PFS of 9 months. Median TTNT was 8 months. Mucositis was the most commonly observed toxicity. This study – the second largest real-world cohort reported to date – underscores the importance of pralatrexate in relapsed/refractory T-cell lymphoma, as well as its acceptable toxicity profile.